Year of the Rat - Richardson, Marc Anthony, 1972- (Book collections on Project MUSE., 2016)
"In the novel, Year of the Rat by Marc Anthony Richardson, an artist returns to the city of his birth to tend to his invalid mother, only to find himself torn apart by memories and longings. Narrated by this nameless figure whose rants, reveries, and Rabelaisian escapades take him on a Dantesque descent into himself, the story follows him and his mother as they share a one-bedroom apartment over the course of a year"--